2023
DOI: 10.4028/p-xxj751
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Activity of CoO/ZnO Nanocrystalline for Dye Wastewater Treatment under UV Light

Abstract: CoO nanocrystal is well-known photocatalyst for overall water splitting. However it suffers from a very short lifetime of only 1 h. The poor stability is derived from carrier recombination-induced thermal oxidation. This research will provide information about synthesis of CoO/ZnO nanocrystalline that can potentially enhance photocatalysts. CoO has been synthesized first under hydrothermal method, followed by calcination process. Thereafter, CoO has been used to produce CoO/ZnO under precipitation method. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Furthermore, the group argues that the oxygen vacancies increased the number of active redox sites and acted as hole traps, enabling their migration to the electrode/electrolyte interface. Another research group [ 14 ] reported the use of ZnO/CoO for the degradation of methylene blue. The group reported that the incorporation of CoO modified the bandgap of the photocatalysts allowing them to degrade methylene blue under visible light in under 3 h.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the group argues that the oxygen vacancies increased the number of active redox sites and acted as hole traps, enabling their migration to the electrode/electrolyte interface. Another research group [ 14 ] reported the use of ZnO/CoO for the degradation of methylene blue. The group reported that the incorporation of CoO modified the bandgap of the photocatalysts allowing them to degrade methylene blue under visible light in under 3 h.…”
Section: Introductionmentioning
confidence: 99%